Pembuatan Batu Tulis Sejarah Desa - Satriawan, Dedi; Rifai, Muhammad; Andriansyah, Rizki; Metia, Elta; Masruroh, Chaula; Anggraini, Putri Bur; Ratnasari, Devi; Fadhilah Harahap, Nur; Zakky Asnawi, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article discusses the history of the founding of Sidomulyo Village in Mesuji District, Mesuji Regency, with a focus on the groundbreaking ceremony as the main milestone in the formation of the village. The main issues raised in this article include the historical background of the village's founding, the process of laying the first stone, and the impact of these activities on the local community. The main target of this research is to identify and analyze the factors that influence the village founding process and understand the significance of the groundbreaking ceremony in the social and cultural context of the Sidomulyo community. The research method used is literature study and direct observation of the laying of the first stone and development of the village. The data obtained was then analyzed to reveal the relationship between the groundbreaking activity and the social changes that occurred in Sidomulyo Village. Making historical inscriptions is used to commemorate the history of the village and local community. In this way, future generations can understand the background and development of Sidomulyo village. Inscriptions are used to commemorate the history of the village and the local community, including establishing village boundaries (sima) and important events in the history of the village. The conclusion of this article shows that the laying of the first stone is not only a symbol of the beginning of the physical development of the village, but also reflects the process of social integration and community participation in the formation of village identity and to commemorate the history of the village. The ceremony plays an important role in building a spirit of togetherness and a sense of belonging among residents, as well as providing a foundation for the village's future development.